Psychophysical assessments of sourness in citric acid-ethanol mixtures - Guirao, Miguelina (2013)
The effect of ethanol in modulating the intensity and duration of the perceived sourness induced by citric acid was studied. Magnitude Estimation-Converging Limits method was applied to rate the sourness of seven solutions (3–70 mM) of citric acid in aqueous solution presented alone and mixed with 8% V/V or 15% V/V ethanol. Dynamic sourness ratings of 5, 15, and 45 mM citric acid alone and mixed with the same two ethanol levels were assessed by the Time Intensity Method (TI). Results were consistent with both methods. Sourness changed with citric acid concentration and ethanol levels. From TI measurements, a similar interactive pattern was obtained for parameters as duration, area under the curve, peak and average intensity.